Evaluation of Effects of Orthodontic Malocclusions on Duration of Treatment with Regard to the Labor/Cost Concept - Mustafa Ersöz; Ebubekir Toy; Ezgi Çakır (Galenos Yayinevi, 2015)
Objective:The purpose of this study was to compare the treatment duration and fees of Angle Class I, II, and III malocclusions.Methods:In this retrospective study, the samples were selected from the files of 450 patients treated at the Department of Orthodontics, İnönü University. The files of patients whose treatments were completed as planned were included in the study. In total, 387 patients (137 males and 250 females) met this criterion (mean age: 14.65 years). Patients were divided into three groups: treatment duration less than 20 months (group A), between 20-30 months (group B), and more than 30 months (group C). Analysis of variance (ANOVA) and t-tests were conducted to determine the difference in treatment duration between the groups and sexes.Results:From the 387 patients, 78 (20.2%) had Class I, 254 (65.6%) had Class II, and 55 (14.2%) had Class III malocclusion. The average treatment duration was 27.82 months (males: 31.82 months, females: 29.33 months). There were no statistically significant differences between the sexes according to the treatment duration. The average treatment duration according to malocclusions was 26.24 months for Class I, 28.22 months for Class II, and 28.21 months for Class III. The distribution of the groups according to treatment duration was as follows: Group A: 72 (18.6%), Group B: 173 (44.7%), and Group C: 142 (36.7%) patients. The relationship between the treatment durations and Angle classifications was not statistically significant (p=0.216).Conclusion:This study showed that there were severe anomalies and problematic malformations within each Angle classification because no statistically significant difference among the malocclusion classes in terms of the duration of treatment was found. Therefore, besides the anomaly type, the treatment duration and effort put into the work should also be taken into consideration in determining the treatment charge.